The Colonial History of Stolen Cultural Artefacts: The British Museum and Its Creditor-Contributors - Muhammed Salman. K (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
Through the deliberate removal and appropriation of cultural artefacts from its colonized areas, the uncomfortable legacy of British colonialism has a dark chapter of a significant cultural upheaval, in addition to its economic exploitation and political domination. This study, which is framed within the notion of extractive colonialism, shows how the British Empire made the British Museum more of an imperial archive, rather than its own professed designation as a national public museum, that too in the disguise of facilitating preservation and academic research. Iconic attractions including the Rosetta Stone, the Elgin Marbles, the Benin Bronzes, the Amaravati Marbles, and the Winged Lions of Nimrud, form a tiny minority among the contested items in the collection of the museum. This study, through regional case studies from Egypt, Greece, India, Nigeria, and Central Asia, discusses how each instance serves as an example of the great colonial reasoning that valued British museological aspirations over indigenous heritage. It also examines the growing international calls for restitution and the monolithic opposition of the Museum that is backed by British legal instruments including the British Museum Act 1963. In addition to identifying the coercive, exploitative, or opaque patterns of acquisition, the paper also reflects on the role of global cooperation frameworks like the 1970 UNESCO Convention in addressing colonial-era state-sponsored cultural theft. Considering how these artefacts act as symbols of national pride, collective memory, and postcolonial resistance, the paper approaches distribution in a larger historical and legal context, rather than dealing with it as a purely moral demand. It argues that as long as the British Museum remain neglectful of the calls for restitution of stolen cultural artefacts, its professed objective of being a custodian of world heritage will remain debated unabated